The Impact of New Ways of Working on Employee Well-Being through Engagement and Job Satisfaction - Simanjuntak, Fransiskus; Rivai, Harif Amali; Syahrul, Laura (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2024)
This study aims to investigate the impact of New Ways of Working (NWW) on Employee Well-Being (EWB) at PT. Bank XYZ, focusing on the roles of Employee Engagement (EE) and Employee Job Satisfaction (EJS) as mediators. A quantitative research design was employed using Partial Least Squares (PLS) analysis. Data were collected via an online survey from 187 respondents at PT. Bank XYZ Region 02, measuring NWW, EWB, EE, and EJS using a 5-point Likert scale. The study found that NWW has a significant direct and indirect impact on EWB, mediated by EE and EJS. The findings emphasize the importance of creating a flexible and supportive work environment to maintain employee well-being and productivity. Therefore, it is recommended that PT. Bank XYZ's management strengthen work location flexibility, provide stress management training, and ensure transparent promotion policies. Additionally, enhancing the work environment through employee recognition and emotional support will contribute to increased productivity and reduced turnover. Strengthening NWW practices, such as flexible work arrangements and the use of supportive technological tools, is crucial to further improve employee well-being and support the organization’s overall goals.